Cultural Diversity: "Reports from Brazil and Argentina" - Célia Regina Rossi; Ana Gouvêa Bochini; Carla Ariela Rios Vilaronga; Luciana Leandro da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article tells two experiences of projects carried through in schools of basic education whose thematic it was the work with the cultural diversity, the valuation of other cultures and reflections on the proper culture The work was carried through in two schools: one in the state of São Paulo, the city of Rio Claro where as the thematic one worked was the Hip-Hop and cultural manifestations local Brazilians the second in the capital of a Argentina province, in the city of Paraná where it worked the contact and the relation enter the cultural manifestations of Brazil and Argentina The central objective of this work was to think ways that could lead to the construction of a school that it considered the differences and the learning that happens when these (the differences) they are in relation.